A Reflection on Low Energy Renovation of Residential Complexes in Southern Europe - Fernando Brandão Alves (2016)
The transformation of European existing building stock towards very low energy buildings requires a new approach. In this context, it seems reasonable to think that buildings should no longer be renovated individually but as part of a global energy system. Focusing on larger urban units may present some scale advantages and may constitute an opportunity to change the urban environment in a smart energy way. Specificities of Southern European countries are addressed. Due either to the climate or the life style, there are large differences in energy consumption per dwelling among southern and northern European countries. How much heating energy will be saved by over-insulating building envelopes if people do not feel the need to heat their houses in the first place? In addition, real energy use in buildings frequently shows major differences with respect to the predicted consumption. The definition of realistic solutions demands the availability of realistic predictions. A case of a residential complex in Portugal is used to illustrate the main questions and to conclude that moving from a building to a group of buildings scale may be an interesting challenge for policy makers to look closer in the near future.